Application of Altman’s Z-score model in predicting business failures of selective hospitality companies in India - D. Souza, Ashley; Chandrashekhar, R. (BOHR International Journal of Finance and Market Research, 2023)
Business failure and bankruptcy are the two words that create panic among stakeholders of the organization. However, with a challenging environment, businesses feel the heat and struggle to make big in the long run. It is recommended to foresee the warning signs and predict business failures to avoid company-specific catastrophes. Numerous predictive models were developed over the last six to seven decades, and among many, Altman’s Z-score model is considered one of the highly reliable models in predicting business failure. The purpose of the research is to find out the financial performance of the companies selected for the study and to identify whether business failure can be predicted in advance to manage future risks. This paper considers Altman’s Z-score model that is used to predict business failures of public companies. A total of 10 hospitality organizations listed in the National Stock Exchange of India are considered for the study. The study analyzes the 5-year financial data from the 2018 to 2022 period. The study reveals that hospitality companies in India are undergoing a difficult phase post-pandemic. Nine out of ten companies selected for the study showed signs of bankruptcy as Altman’s Z-score of companies considered for the study is lower than 1.8 which is in the distress zone.